Validity and reliability malay version of subjective exercise experiences scale (SEES) / Norsyaimaa Athirah Albakeri - Albakeri, Norsyaimaa Athirah (2019)
Background: Exercise and physical activity is one of the most basic human functions and needs which has many benefits in life. Exercises give positive effect on individual physical and mental health. Objective: The aim of this study is to determine the validity and reliability of Malay version of Subjective Exercise Experiences Scale (SEES). Method: This study validate the Malay version of SEES. This study involved validity and reliability phases. Content and face validity has been used. Cronbach alpha is used to determine and measure the internal consistency of the translated instrument. Results: The content validity revealed the acceptable value (0.773). The participants from face validity gave positive feedback about the translated instrument. Psychometric investigation suggested that Malay version of SEES has strong internal consistency with Cronbach alpha of 0.917. The alpha value obtained for three sub-scales of Malay version of SEES is 0.431, 0.957, 0.934. Conclusion: Malay version of Subjective Exercise Experiences Scale (SEES) considered as valid and reliable instrument to assess the experiences or psychological state after exercises among the target populations in Malaysia.